A study on existence : two approaches and a deflationist compromise - Bacigalupo, Giuliano (Cambridge Scholars Publishing, 2017)
The problem of existence is reputed to be one of the oldest and most intractable problems of philosophy: what do we mean when we say that something exists or, even more challengingly, that something does not exist? Intuitively, it seems that we all have a firm grip upon what we are saying. But how should we explain the difference - if any - between statements about existence and other, garden-variety predicative statements? What is the difference between saying that something exists and saying, for instance, that something is red, heavy, or soft? These questions provide the focus for this book.